Sistem Pendataan Keanggotaan pada Kantor Asosiasi Kontraktor Aceh (AKA) - Ziauddin, Ziauddin (KITA Institut, 2020)
The purpose of this study is to design and create a member (company) data processing system at the Bireuen Branch Aceh Contractors Association Office (AKA) so that information about member data becomes more directed and easily obtained and documented. Rapid Application Development (RAD) is used as an application development model. The company's data collection system at the Aceh Contractors Association Office (AKA) follows procedures and uses a computer with the Visual Basic programming language and Microsoft Access database, inputting data in this design is input for business entities, inputting data on deed, inputting data on management, inputting data on labor, inputting on data, work equipment data and input work experience data. The resulting design can explain data based on business entity data reports, work experience reports, business entity management reports, work equipment reports, employment reports and membership card reports.Keywords:System, Data Collection, Membership, Office of the Aceh Contractors Association (AKA).